Serum Gamma glutamyl transferase and Alkaline phosphatase in Acute Cholecystitis - Thapa, P B; Maharjan, D K; Suwal, B (Journal of Nepal Health Research Council, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Background: The serum level of gamma glutaryl transferase and alkaline phosphatase is raised in acute calculus cholecystitis and common bile duct stone. However, the rise in serum level of these enzymes in acute cholecystitis implies stone in the common bile duct is not well studied. Thus, it may lead to retained CBD stone on one side and unnecessary CBD exploration on the other during emergencylaparoscopic cholecystectomy. The objective of the study is to predict presence of CBD stone by assessing serum level ofgamma-glutamyltransferase (gamma-GT) and alkaline phosphatase. Methods: A prospective study was designed which included 40 patients with clinically diagnosed and radiologically confirmed acute cholecystitis and 40 patients who had choledocholithiasis with or without cholangitis. Their serumgamma glutaryl transferase and alkaline phosphatase were analyzed. Results: Both acute cholecystitis and CBD pathology had significant increase in alkaline phosphatase (p-value: 0.05). However, in acute cholecystitis there was 1.69±0.118 fold increase and in CBD pathology there was 2.5±0.57 fold increase in alkaline phosphatase than normal.(130 IU /L). There was no statistically significant difference ingamma- GT in both acute cholecystitis and CBD pathology(p-value: 0.390). However it increases by 2.8±0.47fold in acute cholecystitis and by 2.2±0.16 in CBD pathology (p value: 0.627). <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>Conclusions: Although there is rise in serumϒ-GT and alkaline phosphatase level in acute cholecystitis and CBD stone,only more than 2.5 fold rise in serum alkaline phosphatase level predicts CBD stone. Key Words: Acute cholecystitis, alkaline phosphatase, common bile duct stone, gamma glutaryl transferase